HAJJ FINANCING, DSN MUI, NAHDLATUL ULAMA, PERSIS, ISLAMIC FINANCE PERSPECTIVES - Muhammad Muslih; Mohammad Septian (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
Examines the varied views on talangan haji (hajj financing) in Islamic finance, focusing on the perspectives of key Islamic institutions like the Dewan Syariah Nasional-Majelis Ulama Indonesia (DSN-MUI), Nahdlatul Ulama (NU), and Persatuan Islam (PERSIS). The discussion highlights the ethical and religious debates surrounding the use of financial assistance for haji, traditionally a duty only for those who can afford it without hardship. Talangan haji, essentially a benevolent loan, is scrutinized for its adherence to Islamic principles, especially regarding interest (riba) and the affordability of the pilgrimage. DSN-MUI supports talangan haji, arguing it meets Islamic guidelines by aiding Muslims in fulfilling their religious duties without involving riba. Conversely, NU and PERSIS express concerns; NU worries about the potential dependency on financial schemes that might contradict self-sufficiency in pilgrimage, while PERSIS questions the moral implications of incurring debt for religious purposes, which could compromise the required financial independence. This exploration provides a comprehensive understanding of the intersection between modern financial practices and traditional religious obligations, enhancing the ongoing discourse in Islamic jurisprudence about the relevance of ancient religious practices in contemporary settings.